Tingkat Literasi Digital Mahasiswa Pengguna Aplikasi E-Library Universitas Islam Negeri Raden Fatah - Satria Wijaksana, Muhammad Dewa; Herlina, Herlina (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Digital literacy competency is the ability to process various sources of information based on digital technology, understand the information obtained, and communicate information in digital format. This research seeks to answer the problem formulation in this research, namely: